The Impact of product quality and celebrity endorsment on purchase decision: Brand image as mediation - Ananda, Putri; Hendri, M. Irfani; Purmono, Bintoro Bagus; Rosnani, Titik; Karsim, Karsim (Junal Ilmu Manajemen, 2024)
The tea processing industry has experienced rapid development. Tea production in Indonesia ranks among the top five largest tea-producing countries, with a total production of 136.80 tons in 2022. This creates promising business opportunities for tea beverage enterprises, evident in the proliferation of various contemporary tea-based drinks offered by numerous brands and outlets emerging within Indonesian society. One notable example is Es Teh Indonesia. PT Es Teh Indonesia is a local brand specializing in contemporary tea beverages, established in 2018 and currently operating 945 outlets. This research examines the influence of celebrity endorsement and product quality on purchasing decisions, with brand image as an intervening variable in Es Teh Indonesia. The hypotheses formulated in this study will be tested using causal research. Data collection will be carried out by distributing questionnaires to 225 respondents using purposive sampling techniques. Structural Equation Modeling (SEM) will be employed with the assistance of AMOS 24 for data analysis. The research findings reveal that product quality has a positive and significant impact on brand image, celebrity endorsement has a positive and significant effect on brand image, brand image significant influences purchase decisions, product quality has a positive and significant impact on purchase decisions, and celebrity endorsement positive and significant affects purchase decisions.